Challenges and enablers for creative arts practice in care homes. (1st December 2019) - Evans, Simon Chester; Garabedian, Claire; Bray, Jennifer; Gray, Karen
AbstractThis article reports on the experiences of artists working in UK care homes across residencies that focused on poetry, dance and drama. Data were collected from reflective diaries and focus group discussions to explore the key challenges when working in settings that can be unfamiliar, complex and disruptive. We also describe a range of strategies that artists developed in response to these challenges (enablers) and how this supported successful delivery of their sessions. We conclude that artists need time and support to understand and adapt to the complexity of care homes, and conclude that ultimately the overarching culture of a care home is the key determinant of how successfully artists can facilitate the engagement of residents with meaningful creative activities. Experience of working with people living with dementia can be particularly valuable, as can knowing how to facilitate participation by residents with a range of sensory, physical and cognitive impairments.